Human α1-Antitrypsin Binds to Heat-Shock Protein gp96 and Protects from Endogenous gp96-Mediated Injury In vivo - Lewis, Eli C.; Ochayon, David E.; Mizrahi, Mark I.; Shahaf, Galit; Baranovski, Boris M. (Frontiers in Immunology, 2013)
The extracellular form of the abundant heat shock protein, gp96, is involved in human autoimmune pathologies. In patients with type 1 diabetes, circulating gp96 is found to be elevated, and is bound to the acute-phase protein, α1-antitrypsin (AAT). The two molecules also engage intracellularly during the physiological folding of AAT. AAT therapy promotes pancreatic islet survival in both transplantation and autoimmune diabetes models, and several clinical trials are currently examining AAT therapy for individuals with type 1 diabetes. However, its mechanism of action is yet unknown. Here, we examine whether the protective activity of AAT is related to binding of extracellular gp96. Primary mouse islets, macrophages and dendritic cells were added recombinant gp96 in the presence of clinical-grade human AAT (hAAT, GlassiaTM, Kamada Ltd, Israel). Islet function was evaluated by insulin release. The effect of hAAT on IL-1β/IFNγ-induced gp96 cell surface levels was also evaluated. In vivo, skin transplants were performed for examination of robust immune responses, and systemic inflammation was induced by cecal puncture. Endogenous gp96 was inhibited by gp96-inhibitory peptide (gp96i, Compugen Ltd., Israel) in an allogeneic islet transplantation model. Our findings indicate that hAAT binds to gp96 and diminishes gp96-induced inflammatory responses; e.g., hAAT-treated gp96-stimulated islets released less pro-inflammatory cytokines (IL-1β by 6.16-fold and TNFα by 2.69-fold) and regained gp96-disrupted insulin release. hAAT reduced cell activation during both skin transplantation and systemic inflammation, as well as lowered inducible surface levels of gp96 on immune cells. Finally, inhibition of gp96 significantly improved immediate islet graft function. These results suggest that hAAT is a regulator of gp96-mediated inflammatory responses, an increasingly appreciated endogenous damage response with relevance to human pathologies that are exacerbated by tissue injury.